With Laura: Attachment and the Healing Potential of Substitute Caregivers within Cross-Cultural Child Welfare Practice - Brend, Denise; Fletcher, Kara; Nutton, Jennifer (First Peoples Child & Family Review, 2013)
Secure attachment has been consistently associated with positive outcomes for children. The complex and intergenerational trauma resulting from colonialism that Aboriginal people in Canada have suffered may threaten the development of secure attachment. Using a case example drawn from social work practice, this paper proposes that Aboriginal children who are insecurely attached and traumatized present particular treatment needs. There is little prior research addressing the treatment needs of insecurely attached Aboriginal children in out-of-home care. Further, in provincial and territorial child welfare agencies Aboriginal children are overwhelmingly in the substitute care of non-Aboriginal caregivers. This paper looks to attachment theory for a treatment approach within these cross-cultural relationships. Attachment theory has shown that the attachment styles of children can be reliably predicted at a rate of 75 percent by looking to those of their caregivers. Additionally, children have been shown to be capable of developing multiple attachment styles in response to the attachment styles of the adults with whom they are in caregiving relationships. Thus, given the stronginfluence of caregiver attachment on the attachment styles of children, it is compelling to look at the potential impact of the attachment styles of substitute caregivers on the children in their care. This paper proposes that in provincial or territorial child welfare it may be necessary to promote substitute caregivers who are securely attached and to acknowledge the context of trauma within which these children and caregivers are striving for well-being.